Estudo teórico de pressões em silos esbeltos prismáticos com descarga excêntrica - Deckers, Hellen Pinto Ferreira (2014)
Prismatic vertical silos have been widely executed in Europe and United States for allying high storage capacity to reduced occupation area and easy operation. The interaction between the structure of the silo and the stored product is of great scientific interest since the knowledge on the pressures acting over these units is still scarce. The development of industrial projects of vertical unit factories demand multicellular structures for storing raw materials, adequate for production, given the many types of products used in food processing and formulation. Despite many studies having been conducted on the subject, answers regarding the behavior of the pressures in silos with eccentric discharge, as well as the establishment of a satisfactory calculus procedure considering this type of situation, are lacking. The objective was to estimate the pressures, horizontal and friction, in prismatic slender silos, with square section, eccentric hopper and mass flow using three products with differentiated gradation and outflow. The international norms taken as basis were: AS 3774:1996, DIN 1055- 6:2005 and BS EN 1991-4:2006 and the theories proposed by Safarian (1969) and Walker (1966). The study was conducted in five silo projects with truncated pyramid form hopper considering the following eccentricities: 25%, 30%, 35% and 43%, as well as a concentric model for comparison. For the different gradations, the mass flow was simulated for the products: maize (granular), ground maize (cohesive powder) and soybean meal (powder). The pressures were calculated in slender prismatic silos with eccentric discharge according to the norms (AS 3774:1996, DIN 1055-6:2005 and BS EN 1991-4:2006) and the theories proposed by Safarian and Walker. A computer program was developed in Delphi language for determining the pressures. Based on the results, it may be concluded that, the horizontal and friction pressures in prismatic slender silos with eccentric discharge and mass flow did not present difference for the studied eccentricities for the same norm or theory analyzed, but presented variations regarding the types of product stored. In the determination of the pressures, it is recommended to adopt the data calculation methods by the EUROCODE and DIN norms, paying attention to the combinations of the limit values of the physical properties, which resulted in maximum loadings and the adoption of additional pressures for prismatic silos.